Vocational Students’ Perception of The Use Problem-Based Learning in Speaking English - Nannette Cahyani Janitra; Dian Novita Dewi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study was conducted based on the regulations of the Ministry of Education and Culture related to the teaching and learning process for SMK students, SMK PGRI 3 Malang has attempted to apply problem-based learning methods, which are believed to be methods that help students face real problems in the field. world of work because it can help improve students' speaking skills. Meanwhile, studies on students' perceptions of the use of problem-based learning in their speaking skills are still under-explored. Therefore, this study aims to determine the perception of SMK students about the application of problem-based learning in their speaking skills. This study uses a survey design with SMK PGRI 3 Malang student population, while the sample is 102 students. Data were collected by conducting a survey using a questionnaire. This study's findings imply strengths in applying problem-based learning in the classroom. Furthermore, the researcher revealed that students positively perceived using problem-based learning on their speaking skills.